Identification and validation of hub genes and pathways associated with mitochondrial dysfunction in hypertrophy of ligamentum flavum - Gu, Yifei; Yu, Wenchao; Qi, Min; Hu, Jinquan; Jin, Qianmei; Wang, Xinwei; Wang, Chen; Chen, Yu; Yuan, Wen (Frontiers in Genetics, 2023)
Background: Lumbar spinal stenosis (LSS), which can lead to irreversible neurologic damage and functional disability, is characterized by hypertrophy of ligamentum flavum (HLF). Recent studies have indicated that mitochondrial dysfunction may contribute to the development of HLF. However, the underlying mechanism is still unclear. Methods：The GSE113212 was obtained from the Gene Expression Omnibus (GEO) database, and the differentially expressed genes (DEGs) were identified by R package limma. The intersection of DEGs and mitochondrial dysfunction-related genes (MDRGs) screened from MitoCarta3.0 and GeneCards database were identified as mitochondrial dysfunction-related DEGs (MDRDEGs). Gene Ontology (GO) enrichment analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis and Gene Set Enrichment Analysis (GSEA) were performed using R package clusterProfiler. Protein-protein interaction (PPI) were constructed to screen hub genes, miRNAs and transcriptional factors (TFs) of the hub genes were predicted via miRNet database. Small molecule drugs targeted to these hub genes were predicted via PubChem. Finally, immune infiltration analysis was performed to evaluate the infiltration level of immune cells and their correlation with the hub genes. In final, we validated these results in experiments. Results：In total, 43 genes were identified as MDRDEGs. These genes were mainly involved in cellular oxidation, catabolic processes, and the integrity of mitochondrial structure and function. The top 20 hub genes were screened, including LONP1, TK2, SCO2, DBT, TFAM, MFN2, etc. The most significant enriched pathways including cytokine-cytokine receptor interaction, focal adhesion, etc. Besides, SP1, PPARGC1A, YY1, MYC, PPARG, STAT1 were predicted transcriptional factors of these hub genes. What’s more, increased immune infiltration was demonstrated in HLF, with a close correlation between hub genes and immune cells were found. These results were validated in experiments. Conclusion: This study applied the integrative bioinformatics analysis and revealed the mitochondrial dysfunction-related key genes, regulatory pathways, TFs, miRNAs and small molecules underlying the development of HLF, which improved the understanding of molecular mechanisms and the development of novel therapeutic targets for HLF.